Space cowboys - Lazar, Andrew; Eastwood, Clint, 1930- ([Burbank, CA] : Warner Bros. Pictures, 2000)
Four test pilots who missed their trip to space get a second chance when they are called upon to repair an aging Russian satellite
Executive producer, Tom Rooker ; writer, Ken Kaufman, Howard Klaunsner ; editor, Joel Cox
Cast: Clint Eastwood, Tommy Lee Jones, Donald Sutherland, James Garner
VCD format
Keywords: Space and time in motion pictures